Analysis of the status quo and clinical influencing factors of the social cognitive impairment in deficit schizophrenia - Chengbing, Huang; Jia, Wang; Lirong, Zhuang; Tingting, Zhu; Yanling, Song; Taipeng, Sun; Xiangrong, Zhang (Frontiers in Psychiatry, 2024)
Background: Due to the high heterogeneity of schizophrenia, the factors influencing social cognitive impairment are controversial. The purpose of this study was to investigate the social cognitive dysfunction of deficit schizophrenia (DS), and to explore its clinical impact on the clinical characteristics and neurocognitive function assessment results.Methods: This study involved 100 DS patients, 100 non-deficit schizophrenia (NDS) patients, and 100 healthy controls (HC). Social cognitive functions were assessed using the Eye Complex Emotion Discrimination Task (ECEDT), Game of Dice Task (GDT), and Iowa Gambling Task (IGT), while neurocognitive functions were examined using the Clock Drawing Task (CDT), the Verbal Fluency Task (VFT), Digit Span Test (DST), Stroop Color-word Test (SCWT), and Trail Making Test (TMT). We analyzed the differences in cognitive function among the three groups of patients and the correlation between cognitive function assessment results and Positive and Negative Symptome Scale (PANSS) scores. Results: Comparison of neurocognitive functions among the three groups through CDT, VFT, DST, SCWT, and TMT revealed that in the values of these tests in the DS group differed significantly from those of the NDS and HC groups. However, the DSB of the NDS group was lower and the TMT results were significantly higher than those of the HC group. In the DS group, ECEDT emotion recognition was positively correlated with with stroop colors and stroop interference; the score of gender recognition was positively correlated with VFT, DSF, and SCWT, and TMT-B; the total time spent was positively correlated with TMT; The GDT risky option was negatively correlated with VFT, DST, stroop word, and stroop interference; the negative feedback utilization was negatively correlated with PANSS-Negative; TMT was positively correlated with VFT; IGT was positively correlated with CDT, VFT, DST, and SCWT, but it was negatively correlated with PANSS-Negative and TMT, with statistically significant. Conclusion: There are significant social cognitive impairments in the perception of social information, judgment and resolution of social problems in deficit schizophrenia, which are closely related to negative symptoms and multidimensional neurocognitive dysfunction such as attention, learning, memory, brain information processing speed, cognitive flexibility, and functional executive power.